2004
DOI: 10.1191/1358863x04vm529oa
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial dysfunction and type of cigarette smoked: the impact of ‘light’ versus regular cigarette smoking

Abstract: Acute cigarette smoking leads to temporary endothelial dysfunction, which is an early event in atherogenesis. Sufficient data concerning the effect of cigarettes with low tar and nicotine yield are lacking. Seventeen healthy individuals (nine women, eight men, aged 27.8 AE 3.6 years) were subjected to evaluation of endothelial function by means of endothelium-dependent, flowmediated dilatation (FMD) of the brachial artery, before, immediately after and 30, 60 and 90 min after smoking a regular cigarette (nicot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 11 publications
0
10
0
1
Order By: Relevance
“…Both groups of volunteers presented a significant endothelial dysfunction after smoking the same type of cigarette, which is already described previously [1,[6][7][8]. However, smokers had a more severe endothelial dysfunction than non-smokers according to their total response after smoking one cigarette.…”
Section: Discussionmentioning
confidence: 55%
“…Both groups of volunteers presented a significant endothelial dysfunction after smoking the same type of cigarette, which is already described previously [1,[6][7][8]. However, smokers had a more severe endothelial dysfunction than non-smokers according to their total response after smoking one cigarette.…”
Section: Discussionmentioning
confidence: 55%
“…Papamichael et al 19 investigated acute effects of light and regular cigarette smoking on endothelial function. They found that smoking a regular or light cigarette caused a significant increase in the heart rate immediately after smoking, which was not present 30 minutes after smoking.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we found that smoking light and regular cigaretts has similar effects on heart rate and blood pressure. Papamichael et al found that smoking low-tar, low-nicotine cigarettes is associated with impairment of endothelium-dependent vasodilatation immediately after smoking, which lasts for less than 60 minutes 19. Smoking a cigarette with a higher content of tar and nicotine leads to vasomotor dysfunction lasting at least 60 minutes 19…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the same manner, we observed that light cigarette smoking impairs CFR independently from the nicotine and tar content of the cigarette smoked. Papamichael et al 21 reported that prompt increments in heart rate and BP were observed during the first 5 minutes after smoking. These changes have been attributed to an increase in circulating and locally released catecholamines.…”
Section: Discussionmentioning
confidence: 99%